EFEKTIVITAS BANTUAN LANGSUNG TUNAI BAGI MASYARAKAT TERDAMPAK COVID 19 DI DESA BALAHU KECAMATAN TIBAWA KABUPATEN GORONTALO - Abdul Wahab Podungge; Abdul Madjid Podungge; Dwi Indah Yuliyani Solihin (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This article aims to determine and describe the effectiveness of the direct cash assistance process for people affected by covid 19 in balahu village, tibawa district, gorontalo regency. the research method used is a qualitative method. the data analysis used is an interactive model analysis consisting of three analysis components, namely: 1) data reduction; 2) data presentation; 3) data verification and conclusion drawing. The results of the study show that: (1) in the context of handling the impact of covid 19, especially the economic impact, the balahu village government provides direct cash assistance sourced from village funds which are then distributed to the community through the specified mechanism and time; (2) the effectiveness of the blt program from the aspect of timeliness of blt distribution is on time and follows the existing mechanism. meanwhile, in terms of the accuracy of making choices, the village government has worked according to the procedure. the aspect of targeting accuracy, that the provision of direct village fund cash assistance is right on target.